Nectar Resource Use by Butterflies in a Dry Deciduous forest in Eastern Ghats, India - Selvarathinam, T.; Balasubramanian, P.; Kumaravelu, G. (Indian Forester, 2009)
This paper discusses the butterfly- flower interrelationships in a dry deciduous forest in Sathyamangalam Wildlife Sanctuary, Tamil Nadu, Eastern Ghats. A total of 86 species of butterflies belonging to five families were recorded in the study area. Butterfly foraging observations were recorded on 27 plant species belonging to 17 families. A total of 49 species of butterflies foraged on floral nectar of 21 plant species. Maximum number of flower-visiting butterfly species (n=17) belonged to Nymphalidae. Small-sized flowers (<1cm) attracted maximum number of butterfly species (n=48). Among the various flower colours, red were visited by maximum number of species (n=36). Mud-puddling behaviour of butterflies is also discussed.